(untitled) (Bangladesh Journal of Medical Science, 2014)
Background and Aims: A substantial number of diabetic patients, diagnosed at relatively younger age, who dont fit to typical type 2 and type 1 class of diabetes. These patients usually present with very high level of glycemia. The uniqueness of this group of patient provide the opportunity to explore the pathophysiology of nerve functional status at an early stage of diabetes. The present study was aimed to determine markers of endothelial dysfunction and evaluate nerve functional status of a group of newly diagnosed clinically uncomplicated young diabetic patients. Material and Methods: A total number of 32 (male-13 and female-19) newly diagnosed young (diabetes diagnosed under 30 yrs) were consecutively recruited from BIRDEM Out-patient department and 30 age-, BMI-matched healthy subjects with no family history of diabetes up to second generation served as controls. Serum fructosamine was measured by reduction test with NBT method. Serum C-peptide, endothelin-1 and tissue plasminogen activator (t-PA) by ELISA and von Willebrand factor (vWF) by Radial Immunodiffusion (RID) methods. Urinary albumin measured by immunoturbidimetry method. Nerve functional status was evaluated by nerve conduction velocities (NCV), distal latencies (DL), compound muscle action potential (CAMP), F wave latencies (FWL), nerve action potential (SNAP) for motor and sensory nerve as appropriate following the standard protocol. Results: Severe hyperglycemia in the diabetic group was reflected in their mean (SD) fasting C-peptide and fructosamine level. Altered endothelial dysfunction, as evidenced by significantly high tissue plasminogen activator (t-PA) (p<0.001) in the diabetic group. Albumin creatinine ratio (ACR) was almost similar in the two groups. Ulnar distal latency was similar in both the groups. But its CAMP and NCV were significantly lower in the diabetic group (p<0.02-0.001). Ulnar F wave latency were significantly higher (p=0.016) in the diabetic group. Ulnar sensory conduction parameters did not show any difference between two groups. Peroneal motor and sural sensory functional status of the diabetic subjects showed similar trend like that of ulnar motor and sensory status. Peroneal nerve motor NCV was significantly negatively correlated with fasting glucose [r=- 0.456, p=0.001]. Peroneal motor distal latency was significantly correlated with fasting fructosamine [r=0.439, p=0.012]. Fasting fructosamine showed significant negative correlation with motor peroneal NCV [r=-0.572, p=0.001], motor ulnar NCV [r=-0.468, p=0.007], both ulnar and sural sensory NAP (p=0.02 for both]. On the basis of F wave latency 53% of diabetic subjects had diabetic neuropathy and markedly higher t-PA compared to nonneuropathy groups (p=0.001). Conclusions: The data suggest that (i) Young type 2 diabetic subjects had endothelial dysfunction at the time of diagnosis even in the presence of normoalbuminuria state; (ii) Motor nerve conduction parameters are affected more than the sensory component; (iii) F wave latencies are more frequently and early to be involved in these subjects and linked to high serum t-PA. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18302 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.190-197